Kedudukan Akad Dalam Perspektif Ekonomi Islam - Hardiati, Neni; F, Fitriani; Wahyuni, Eka (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Contracts are of various kinds of tasharruf, namely "everything that comes out of a human being with his will and the syara' stipulates some of his rights". In muamalah activities, the contract is an inseparable part of a series of transactions or agreements on the contract itself. The most important aspect of muamalat fiqh in contracting with Islamic economics is transaction law (law) which includes general contract principles and specific provisions for various specific contracts. One aspect of the general contract is about the pillars and terms of the contract as an element of forming the contract. In the practice of buying and selling muamalat, there are pillars and conditions that make a sale and purchase valid including 3 (three) things, namely; the contract, the contract (the existence of goods), and the prayers of the people in the contract.